Gordis epidemiology - Celentano, David D.; Szklo, Moyses (Elsevier, 2019)
This bestselling text provides a solid introduction to basic epidemiologic principles as well as practical application in public health and clinical practice, highlighted by real-world examples throughout. New coverage includes expanded information on genetic epidemiology, epidemiology and public policy, and ethical and professional issues in epidemiology, providing a strong basis for understanding the role and importance of epidemiology in today's data-driven society. -- From publisher's description